CO2 and CH4 isotope compositions and production pathways in a tropical peatland. Issue 1 (6th January 2015) - Holmes, M. Elizabeth; Chanton, Jeffrey P.; Tfaily, Malak M.; Ogram, Andrew
Abstract While it is widely recognized that peatlands are important in the global carbon cycle, there is limited information on belowground gas production in tropical peatlands. We measured pore water methane (CH4) and carbon dioxide (CO2) concentrations and δ13C isotopic composition and CH4 and CO2 production rates in peat incubations from the Changuinola wetland in Panama. Our most striking finding was that CH4 was depleted in 13C (−94‰ in pore water and produced at −107‰ in incubated peat) relative to CH4 found in most temperate and northern wetlands, potentially impacting the accuracy of approaches that use carbon isotopes to constrain global mass balance estimates. Fractionation factors between CH4 and CO2 showed that hydrogenotrophic methanogenesis was the dominant CH4 production pathway, with up to 100% of the CH4 produced via this route. Far more CO2 than CH4 (7 to 100X) was measured in pore water, due in part to loss of CH4 through ebullition or oxidation and to the production of CO2 from pathways other than methanogenesis. We analyzed data on 58 wetlands from the literature to determine the dominant factors influencing the relative proportions of CH4 produced by hydrogenotrophic and acetoclastic methanogenesis and found that a combination of environmental parameters including pH, vegetation type, nutrient status, and latitude are correlated to the dominant methanogenic pathway. Methane production pathways in tropical peatlands do not correlate with these variables in the same way as their more northerly counterparts and thus may be differently affected by climate change.